2021
DOI: 10.18231/j.ijogr.2019.041
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study to evaluate the relation between thyroid disorders and abnormal uterine bleeding in reproductive age group

Abstract: Introduction: Abnormal uterine bleeding (AUB) is a common disorder occurring in reproductive age group females. It can be understood as bleeding that occurs from the uterus outside the normal parameters and there is no structural defects in the genital tract. One of the most common association with AUB is thyroid dysfunctions. Hence this study aimed to see the incidence of thyroid related disorders in AUB and also to assess the menstrual pattern. Material and Methods: 100 women suffering from AUB who presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
2
2
0
1
Order By: Relevance
“…. Similar flux of population was reported in a study in which the majority of females presented with AUB were euthyroid (77%) and 23% were affected with thyroidism, while, our findings revealed that 71.87% AUB patients were euthyroid and 28.13% were affected with thyroid disorders 3,14,15 . Similar findings were reported that most patients presented with AUB were from category of euthyroid and the menorrhagia was the common matter of complain 16 .…”
Section: Examination Of the Patientssupporting
confidence: 90%
See 3 more Smart Citations
“…. Similar flux of population was reported in a study in which the majority of females presented with AUB were euthyroid (77%) and 23% were affected with thyroidism, while, our findings revealed that 71.87% AUB patients were euthyroid and 28.13% were affected with thyroid disorders 3,14,15 . Similar findings were reported that most patients presented with AUB were from category of euthyroid and the menorrhagia was the common matter of complain 16 .…”
Section: Examination Of the Patientssupporting
confidence: 90%
“…The association of thyroidism was also compared with AUB incidence in different age groups of the females and it was evident from the results that significantly highest (p<0.05) incidence of AUB due to thyroid abnormities was seen in the age Group C (39-50 years) (78.57%) and Group A (13-25 years) (38.15%), while, 4). The findings of our study were in accordance with the studies in which the prevalence of AUB due to thyroid disorders was highest in old age females 3,13 . Another study stated that 67.2% of the female patients of age 35-45 years were affected with AUB due to thyroid disorders 17,18 .…”
supporting
confidence: 92%
See 2 more Smart Citations
“…В останні роки суттєво збільшилася частота аномальних маткових кровотеч (АМК) у жінок репродуктивного віку на тлі екстрагенітальної патології [4,5,6]. Незважаючи на значну кількість наукових досліджень з проблем АМК, питання особливостей соматичного та гінекологічного анамнезу, клінічних проявів АМК у жінок з патологією щитоподібної залози потребує більш глибокого вивчення для подальшого розроблення методів їх профілактики.…”
unclassified